Online shopping during MCO: what consumers should know in dealing with sellers on social media? / Suria Fadhillah Md Pauzi, Azniza Ahmad Zaini and Muhammad Asyraf Azni - Md Pauzi, Suria Fadhillah; Zaini, Azniza Ahmad; Azni, Muhammad Asyraf (Universiti Teknologi MARA, 2021)
The application of online platform as a method to shop has grown rapidly especially during the Movement Control Order. Online shopping has become a trend and an easy method to purchase goods without any necessity to go out from home, and get everything we want by browsing and later on do our purchase through the respective websites. Recently, the Prime Minister has unveiled a new short-term economic recovery plan called PENJANA in order to boost the economy due to the outbreak by allocating RM 70 million under its Shop Malaysia Online campaign for Malaysians to encourage domestic spending while following the requirements of new norms. However, the complex nature of e-commerce may lead to the ambiguity on the legal rights of the consumers especially when the seller breaches the contract. This paper examines the current issues on online shopping through social media such as Facebook and the information that consumers need to know in order to protect their legal rights with reference to selected legislations pertaining to the online purchase issues. Advancement of technology with consumers without adequate knowledge become a handicap for the consumers in making effective decisions to protect their rights and in becoming a resilient millennium community.